Knowledge About Tuberculosis and Multi-Drug Resistant Tuberculosis Among Interns - Rupali A Patel; Gautam M Khakse (National Journal of Community Medicine, 2014)
Background: Tuberculosis (TB) is an ancient disease with new threats of Multi-drug resistant (MDR-TB) and Extensively drug resistant tuberculosis (XDR-TB). To treat and prevent this every health care personnel should have a thorough knowledge of it. Internship is a crucial period when knowledge is applied practically.